Appendectomy Is Oncologically Equivalent to Right Hemicolectomy for Well-Differentiated T1 Appendiceal Adenocarcinoma. Issue 1 (18th August 2022) - AlMasri, Samer S.; Hammad, Abdulrahman Y.; Singhi, Aatur D.; Paniccia, Alessandro; Zureikat, Amer H.; Celebrezze, James P.; Choudry, Haroon A.; Nassour, Ibrahim
Abstract : BACKGROUND: Right hemicolectomy is recommended for appendiceal adenocarcinoma but may not be needed for early stage disease. OBJECTIVE: This study aimed to determine whether appendectomy offers adequate oncologic outcomes for T1 appendiceal adenocarcinoma from a national cohort of patients. DESIGN: Patients with T1 appendiceal adenocarcinoma (mucinous and nonmucinous histology) treated with either a right hemicolectomy or appendectomy between 2004 and 2016 were retrieved. Multivariate Cox regression analysis was used to identify predictors of overall survival. SETTING: The study was conducted using a national cancer database. PATIENTS: A total of 320 patients (median age, 62 y; 47% women) were identified: 69 (22%) underwent an appendectomy and 251 (78%) underwent a right hemicolectomy. MAIN OUTCOME MEASURE: Overall survival was measured. RESULTS: Nonmucinous adenocarcinoma was identified in 194 (61%), whereas 126 (39%) had mucinous adenocarcinoma. Of the overall cohort, 43% had well-differentiated histology, 39% had moderately differentiated disease, and 4% had poorly differentiated tumors. The rate of lymph node metastasis was lower in well-differentiated tumors (3%) compared with moderately (10%) or poorly differentiated tumors (25%). On univariate survival analysis, right hemicolectomy was associated with improved 1-, 3-, and 5-year overall survival in patients with moderately/poorly differentiated disease ( p < 0.001) but not for well-differentiated disease ( p = 1.000). After adjustment, right hemicolectomy was associated with overall survival improvement for moderately/poorly differentiated T1 adenocarcinoma (HR = 0.26 [95% CI, 0.08–0.82]; p = 0.02) but not for well-differentiated disease. LIMITATIONS: This study was limited by its retrospective nature. CONCLUSIONS: The current analysis from the National Cancer Database demonstrates that appendectomy is associated with equivalent survival to right hemicolectomy for well-differentiated T1 adenocarcinoma, whereas for moderately and poorly differentiated disease, right hemicolectomy is oncologically superior to appendectomy. See Video Abstract at http://links.lww.com/DCR/B689 . LA APENDICECTOMÍA ES ONCOLÓGICAMENTE EQUIVALENTE A LA HEMICOLECTOMÍA DERECHA PARA EL ADENOCARCINOMA APENDICULAR T1 BIEN DIFERENCIADO: ANTECEDENTES: La hemicolectomía derecha se recomienda para el adenocarcinoma apendicular, pero puede no ser necesaria para la enfermedad en estadio temprano. OBJETIVO: Este estudio tuvo como objetivo determinar si la apendicectomía ofrece resultados oncológicos adecuados para el adenocarcinoma apendicular T1 de una cohorte nacional de pacientes. DISEÑO: Se recuperaron pacientes con adenocarcinoma apendicular T1 (histología mucinoso y no mucinoso) tratados con hemicolectomía derecha o apendicectomía entre 2004–2016. Se utilizó un análisis de regresión de Cox multivariante para identificar los predictores de la supervivencia global. ENTORNO CLÍNICO: Base de datos nacional sobre cáncer. PACIENTES: Se identificaron un total de 320 pacientes (mediana de edad 62 años, 47% mujeres): 69 (22%) se sometieron a una apendicectomía y 251 (78%) se sometieron a una hemicolectomía derecha. PRINCIPAL MEDIDA DE RESULTADO: Sobrevida global. RESULTADOS: Se identificó adenocarcinoma no mucinoso en 194 (61%) mientras que 126 (39%) tenían adenocarcinoma mucinoso. De la cohorte general, el 43% tenía una histología bien diferenciada, el 39% tenía una enfermedad moderadamente diferenciada y el 4% tenía tumores poco diferenciados. La tasa de metástasis en los ganglios linfáticos fue menor en los tumores bien diferenciados (3%) en comparación con los tumores moderadamente (10%) o pobremente diferenciados (25%). En el análisis de sobrevida univariante, la hemicolectomía derecha se asoció con una mejor sobrevida general a 1, 3, y 5 años en pacientes con enfermedad moderada / pobremente diferenciada ( p < 0, 001) pero no para la enfermedad bien diferenciada ( p = 1, 000). Después del ajuste, la hemicolectomía derecha se asoció con una mejora de la sobrevida general para el adenocarcinoma T1 moderadamente / poco diferenciado (HR = 0, 26, IC del 95%: 0, 08–0, 82, p = 0, 02) pero no para la enfermedad bien diferenciada. LIMITACIONES: Este estudio estuvo limitado por su naturaleza retrospectiva. CONCLUSIONES: El análisis actual de la base de datos nacional de cáncer demuestra que la apendicectomía se asocia con una sobrevida similar a la hemicolectomía derecha para el adenocarcinoma T1 bien diferenciado, mientras que para la enfermedad moderada y pobremente diferenciada, la hemicolectomía derecha es oncológicamente superior a la apendicectomía. Consulte Video Resumen en http://links.lww.com/DCR/B689 . (Traducción—Dr. Yazmin Berrones-Medina )